2020
DOI: 10.1021/acs.jafc.0c02828
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Short-Clustered Maltodextrin as Starch Substitute for Ameliorating Postprandial Glucose Homeostasis

Abstract: Dietary starch is usually associated with elevated postprandial glycemic response. This is a potential risk factor of type 2 diabetes. Here, a 1,4-α-glucan branching enzyme (GBE) was employed to reassemble α-1,4 and α-1,6 glycosidic bonds in starch molecules. Structural characterization showed that GBE-catalyzed molecular reassembly created an innovative short-clustered maltodextrin (SCMD), which showed a dense internal framework along with shortened external chains. Such short-clustered molecules obstructed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 81 publications
3
27
0
Order By: Relevance
“…Therefore, we can conclude that the branch points provide greater protection to butyl groups from enzymatic hydrolysis, given the distributional difference of butyl groups at the molecular level. Similar results regarding the hydrolysis of glycosidic bonds have been reported in a previous study, where increased branch points significantly weakened the enzymatic susceptibility of starch molecules …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, we can conclude that the branch points provide greater protection to butyl groups from enzymatic hydrolysis, given the distributional difference of butyl groups at the molecular level. Similar results regarding the hydrolysis of glycosidic bonds have been reported in a previous study, where increased branch points significantly weakened the enzymatic susceptibility of starch molecules …”
Section: Discussionsupporting
confidence: 90%
“…Similar results regarding the hydrolysis of glycosidic bonds have been reported in a previous study, where increased branch points significantly weakened the enzymatic susceptibility of starch molecules. 43 Correlation between Intestinal Digestion and Colonic Fermentation. Previous studies have provided important insights into the role of starch structure in the fermentation process of resistant starch.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The increased branching density is accompanied by reduced digestibility (Ao et al, 2007;Kong et al, 2021). Higher SDS and RS contents have been reported for maize (Li et al, 2014) and tapioca (Ren et al, 2018) starches when modified by branching enzymes from Acidothermus cellulolyticus 11B and Geobacillus thermoglucosidasius STB02, respectively.…”
Section: Shortening Of Ap Chains and Increasing Branching Densitymentioning
confidence: 90%
“…SCMD was enzymatically synthesized using our earlier reported procedures (moisture content, 4.3%; protein content, 0.45% [w/w, dry basis]; purity, >99% [w/w, dry basis]) . MD, which showed a weight-average molecular mass similar to that of SCMD, was produced as previously detailed .…”
Section: Methodsmentioning
confidence: 99%
“…The product of the enzymatic approach displayed a higher branching density and contained more abundant short branches polymerized by 2–8 glucose units, as compared with the native starch or normal maltodextrin. Therefore, it was referred to as short-clustered maltodextrin (SCMD) . We have also found that the SCMD induces an attenuated glycemic response in ICR mice and is feasible to alleviate the glucose metabolism disorder in db / db mice with type 2 diabetes .…”
Section: Introductionmentioning
confidence: 99%